Interaction in e-learning and its relationship to the personal knowledge of students from the point of view of faculty members - Ghassan Kahdim Jabber ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
Does the interaction of students in E-learning and the practice of teaching skills differ according to the teachers’ personal knowledge of them and the individual differences between them? With this question, the research problem created, and the author will be exposed to this question with a number of special aspects emanating from the realistic social interaction between the teaching staff and students in the classroom in particular and the college in general, and its difference between the interaction between the teaching and students in virtual reality through E-learning. DOI /10.54633/2333-021-042-013